Identification of Students' Misconceptions Using a Four-Tier Multiple Choice Diagnostic Test on Colligative Properties of Solutions - Aisyah Nur Pratiwi; Erlina Erlina; Ira Lestari; Masriani Masriani; Rahmat Rasmawan (Jurnal Penelitian Pendidikan IPA, 2023)
Misconception is an event of a wrong concept received by students after following a learning process, the concept received is not in accordance with existing scientific studies. This study aims to identify students' misconceptions on the colligative properties of the solution and the factors that cause misconceptions. This type of research is descriptive quantitative. The instrument used is a four-tier multiple choice diagnostic test. This study involved 34 students of class XII MIA at MA Khulafaur Rasyidin Sungai Raya. The results showed that the level of misconceptions of students had an average percentage of 34% with a moderate misconception category, where a total of 65% students experienced misconceptions in the sub-topic of vapor pressure depression, 26,30% students experienced misconceptions in the sub-topic of freezing point depression, Â 33,30% students experienced misconceptions in the sub-topic of boiling point elevation, and Â 26% students experienced misconceptions in the sub-topic of osmotic pressure. Based on the results of the interview, the factors causing misconceptions in this study consist of internal and external factors. Internal factors come from students, that are students provide concept ideas spontaneously based on their understanding without being investigated first, students provide incorrect reasoning, students are confused in connecting one concept with another, lack of interest and ability of students in learning chemistry. External factors come from the context and teaching methods, where one of the learners' discussion partners has misconceptions, the teacher is more dominant in providing chemical explanations in mathematical form, and limited experiments. Those misconceptions can be reduced by presenting the topic in an interesting way, using an experiment, or using multiple representations approach.